2000
DOI: 10.1111/j.1749-6632.2000.tb06236.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Oral Contraceptive Treatment of Adolescent Girls with Polycystic Ovary Syndrome: Lipid Profile

Abstract: The clinical signs and neuroendocrine features of adolescents with polycystic ovary syndrome (PCOS) resemble those found in adult women with PCOS. These adolescent patients are candidates for long-term treatment by one of the different therapeutic approaches that have been proposed. It is therefore essential that the treatment does not induce unfavorable metabolic effects. We investigated and compared the effects of cyproterone acetate (CA) and desogestrel (D), as part of combined oral contraceptives (COC), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Our result is similar to that of previous study conducted by Creatsas G et al 8 Our results suggested that Ethinyl estradiol and Cyproterone acetate combination was effective for PCOS patients when compared to norethisterone.…”
Section: Figure 8 Comparison Of Androgenic Symptoms Studiessupporting
confidence: 83%
“…Our result is similar to that of previous study conducted by Creatsas G et al 8 Our results suggested that Ethinyl estradiol and Cyproterone acetate combination was effective for PCOS patients when compared to norethisterone.…”
Section: Figure 8 Comparison Of Androgenic Symptoms Studiessupporting
confidence: 83%
“…Creatsas et al [46], Luque-Ramierz et al [47], Lemay et al [48], Falsetti et al [49] described consistent reduction in hirsutism scores (F-G and mF-G) in all areas of the body. Kahraman et al [46] describe more prominent changes in specific body areas, for example, the abdomen.…”
Section: Efficacy In Hyperandrogenic Skin Symptoms Of Pcosmentioning
confidence: 96%
“…Creatsas et al [46], Luque-Ramierz et al [47], Lemay et al [48], Falsetti et al [49] described consistent reduction in hirsutism scores (F-G and mF-G) in all areas of the body. Kahraman et al [46] describe more prominent changes in specific body areas, for example, the abdomen. In an openlabel study, Golland and Elstein [50] reported a healing/ improvement rate of 54.6% (reduction in mean F-G score from 14.3 to 5.7) at 12 months with CPA/EE in 22 women with severe facial hirsutism.…”
Section: Efficacy In Hyperandrogenic Skin Symptoms Of Pcosmentioning
confidence: 96%
See 2 more Smart Citations